Detection of Leptospira spp. in Selected National Service Training Centres and Paddy Fields of Sarawak, Malaysia using Polymerase Chain Reaction Technique - Chai, Fung Pui; Lesley Maurice, Bilung; Lela, Su’ut; Yee, Ling Chong; Kasing, Apun (Universiti Putra Malaysia, 2017)
Leptospirosis is a zoonotic disease which is caused by spirochetes from the genus Leptospira. It can be transmitted to humans through direct contact with infected animals or indirect contact with an environment contaminated by the urine of infected animals. The objective of this study was to study the status of leptospirosis in two selected National Service Training Centres (NSTCs) and two paddy fields of Sarawak. A total of 31 captured rats, 210 soil samples and 210 water samples were collected from these study sites. All the samples were inoculated into a modified semisolid Ellinghausen-McCullough-Johnson- Harris (EMJH) broth with 5-fluorouracil. For soil and water samples, a specific polymerase chain reaction (PCR) was conducted after a one-month incubation period. Kidney and liver samples from rats were incubated and PCR was carried out monthly during the threemonth incubation period. Representative PCR-positive samples which targetted LipL32, 16S rRNA and rrs genes at 423 bp, 331 bp and 240 bp in pathogenic, intermediate and saprophytic Leptospira, respectively, were further sequenced. From the PCR analysis, intermediate Leptospira was detected in one (3.2%) rat species, Rattus exulans, that was captured in a paddy field. A total of six (2.9%) pathogenic Leptospira, one (0.5%) each from intermediate and saprophytic Leptospira, were present in soil samples from the study sites. Six (2.9%) water samples were contaminated by pathogenic Leptospira, four (1.9%) by intermediate Leptospira and seven (3.3%) by saprophytic Leptospira. All the contaminated environmental samples were collected from NSTCs except for two soil samples and four water samples from paddy fields that were infected by pathogenic Leptospira. Results from DNA sequencing analysis indicated that the dominant pathogenic, intermediate and saprophytic Leptospira species circulating in these study sites were Leptospira noguchii, Leptospira wolffii serovar Khorat and Leptospira meyeri, respectively. Although the prevalence of Leptospira is low, there is still a risk of infection to those who are involved in outdoor activities at training centres and paddy fields. Control and preventive measures are, therefore, important in tackling preventable diseases related to pathogenic Leptospira